The Monastic Patronage of Bishop Alexander of Lincoln - Dyson, A. G. (The journal of ecclesiastical history, 1975)
In a particularly active, if sadly undocumented, period in the history of the English Church, Alexander, third bishop of Lincoln (1123–1148), stands out as a prelate of unusual energy and achievement. Beyond his intermittent involvement in national affairs, he was responsible in the twenty-five years of his episcopate for the establishment of at least nine prebends in the Lincoln chapter; the acquisition of substantial assets for his see—including the right of market and fair in two towns; the setting up of an additional and final, archdeaconry; extensive structural and decorative innovations at his cathedral; the founding of at least one leper hospital; the erection of two, and very probably three, castles; and the establishment of four religious houses. The last of the activities in this impressive curriculum, the founding of the Cistercian houses of Thame and Louth, the Arrouaisian house of Dorchester and the Gilbertine house of Haverholm, all in the brief period 1139–41, represents an achievement approached at that time only by the three foundations of bishop Warelwast of Exeter (1107–37) at Plympton, Launceston and Bodmin. If, moreover, Alexander was not the formal founder of the Gilbertine house of Sempringham some years earlier, it is at least clear that he played a decisive role there, as, indeed, there is good reason for supposing that he made a more positive and critical contribution to the early development of this, the only indigenous English monastic order, than has previously been allowed.